Kajian Ilmu Falak Syaikh Muhammad Arsyad Banjar: Analisis Naskah Mas'alah Al-Qiblah Fi l-Batawy - Arwin Juli Rakhmadi; Hasrian Rudi Setiawan; Muhammad Hidayat (Perpustakaan Nasional RI, 2022)
Shaykh Muhammad Arsyad Banjar is a figure of fiqh and astronomy Nusantara who has a great influence on Islamic scholarly discourse in Nusantara. One of his astronomical works is Mas’alah al-Qiblah fi l-Batawy which discusses various issues of Qibla direction that developed in the community, especially among Baetawi residents at that time. This manuscript is stored in UB Leiden, Netherlands. This manuscript provides information about the dynamics of Islam that developed in society at that time, especially in matters of Qibla direction. This manuscript also informs that the phenomenon of the inaccuracy of the Qibla direction of a mosque at that time. Shaykh Muhammad Arsyad Banjar with his knowledge reconstructed the Qibla direction, including with naqli arguments, then tested directly with calculations and tools, one of the tools used was a compass (bait al-ibrah). In reality he received rejection and opposition from a number of figures and the community at that time. This study is intended to reveal this phenomenon which is represented in the Mas’alah al-Qiblah fi l-Batawy manuscript.